2020
DOI: 10.5194/egusphere-egu2020-7531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Neotethys suture in the eastern Bulgarian Rhodopes

Abstract: <p>Following a tectonic scheme proposed by Janák et al. (2011; Journal of Metamorphic Geology 29, 317-332) and Pleuger et al. (2011; Zeitschrift der Deutschen Gesellschaft für Geowissenschaften 162, 171-192), the Rhodopes are composed of four nappe complexes, from bottom to top the Lower, Middle, and Upper Allochthon and the Circum-Rhodope Belt. Rocks derived from Adria and/or Pelagonia (Lower Allochthon) are separated from rocks of European origin (Upper Allochthon) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…5; Luda Reka ophiolite, Pleuger et al, 2020). Pleuger et al (2020) presented new U-Pb LA-ICP-MS zircon ages of 163.5±2.6 Ma from an amphibolite and 154.2±1.0 Ma from a metagabbro sample. The reported trace element patterns of the metagabbro sample resemble those of typical back-arc basalts and lower oceanic crustal cumulates and the initial ε-Nd values of average basalts derived from depleted ambient mantle.…”
Section: Kimi-krumovitsamentioning
confidence: 96%
See 4 more Smart Citations
“…5; Luda Reka ophiolite, Pleuger et al, 2020). Pleuger et al (2020) presented new U-Pb LA-ICP-MS zircon ages of 163.5±2.6 Ma from an amphibolite and 154.2±1.0 Ma from a metagabbro sample. The reported trace element patterns of the metagabbro sample resemble those of typical back-arc basalts and lower oceanic crustal cumulates and the initial ε-Nd values of average basalts derived from depleted ambient mantle.…”
Section: Kimi-krumovitsamentioning
confidence: 96%
“…These eclogites were described as ophiolitic fragments which have experienced UHP conditions during the Middle Jurassic (Bonev et al, 2015a) or the Eocene (Mposkos et al, 2012) subduction. In fact, they are probably part of the Kimi-Krumovitsa Unit, where numerous meta-ophiolitic sequences of Devonian (Peytcheva et al, 2018) to Late Jurassic age (Pleuger et al, 2020), were reported.…”
Section: Protolithmentioning
confidence: 99%
See 3 more Smart Citations